Intelligent elderly care - Kho, Kristie Yee Cheng (2018)
An ageing population leads to an increasing number of elderly living independently. Living independently at an old age entails a certain amount of risk such as a fall that goes unnoticed or dementia triggered by social isolation. This project seeks to reduce the burden on adults providing support, and at the same time able to monitor the well-being and safety of elderly living independently. Falls – the second leading cause of unintentional injury for people of all ages and leading cause of death for elderly aged 65 and above. Early detection of a fall is crucial to minimize the chances of critical injury. Various fall detection approach are available such as the wearable, ambience and computer-based approach. However, some of these approaches are expensive, inaccurate or unsuitable for outdoor use. Living independently may prove difficult for the elderly with mild to moderate dementia due to deteriorating cognitive functions and a limited support network. Cases of elderly with or without dementia going missing are commonly encountered. Thus, monitoring the frequency at which the elderly leaves or returns home is necessary. Various approaches are available that make use of motion sensors and Radio Frequency Identification. However, some are proven to be inaccurate, and they are not tailored specifically to serve the elderly. Two systems will be developed in light of the issues raised above –a wearable device, and a door monitoring system based on Radio Frequency Identification for tracking movements of the elderly in and out of their home. The prototype system is designed with affordability, user-friendly and functionality in mind. Additional functions such as SMS notifications, GPS localisation, LCD reminder system and a panic button will be incorporated to enhance the functionality of the system. Two prototype devices were successfully built and tested with a great degree of accuracy and robustness. No society can overlook the social and structural issues accompanying an aging population, for negligence in this area leads to dire consequences. Thus, more research should be devoted into improving the lives of the elderly using the technology available.